Effect of the aeration system on water quality parameters and productive performance of red tilapia ( Oreochromis sp.) grown in a biofloc system (2023)
The objective of this work was to assess the performance of two aeration types, splash and blower, used on a commercial biofloc technology (BFT) farm of red tilapia, Oreochromis sp., and their effect on growth performance and water quality parameters. For this, red tilapia juveniles were randomly distributed into twelve tanks. Each tank had an independent aeration system, and two experimental groups were characterized: six tanks used splash aerators (SPL group; one per tank, 1 hp), and the remaining tanks used a blower aerator (BLW group) with the same potency (1 hp). Water quality parameters were registered daily, and after 90 days of commercial culture, we obtained final growth parameters for each batch (tank). We observed no statistical differences on growth parameters, while water quality parameters showed that dissolved oxygen and oxygen saturation were significantly higher for the SPL group. Therefore, this field study corroborated indications from prior research at laboratory conditions that, at a commercial scale, splash aerators are more adequate for the production of red tilapia in BFT conditions.